Retrospective Analysis of Traumatic Injuries to the Facial Skull Bone - Lytovchenko, Наталія; Vasyliev, Олександр (Actual Dentistry, 2026)
Introduction. Up-to-date statistical data on maxillofacial injuries, including incidence and hospitalization patterns, are lacking. Such data are essential for evaluating the effectiveness of preventive and therapeutic measures, improving emergency care delivery, and identifying systemic issues within the specialty of maxillofacial surgery. Objective. To conduct a statistical analysis of hospitalization patterns in emergency maxillofacial surgery. Material and Methods. Medical records of 15,227 patients hospitalized between 2018 and 2022 were analyzed. Statistical processing was performed using mean values and extensive indicators. Results. The number of patients with emergency maxillofacial pathology remains consistently high, with no tendency toward decline. The majority of hospitalized patients were young, working-age men. Of all hospitalizations, 28.6% were self-referred patients, and 22.9% were from outside the city. The average length of stay was 3.85 days and remained stable throughout the study period. The injury structure was dominated by maxillofacial wounds and mandibular fractures. Osteosynthesis was performed in 29.9% of mandibular fracture cases. Up to 70% of patients required follow-up care by a maxillofacial surgeon after discharge. Mortality was extremely low and attributable to severe comorbid conditions.